Cellular FLICE-like inhibitory protein secures intestinal epithelial cell survival and immune homeostasis by regulating caspase-8. - Günther, Claudia; Martini, Eva; He, Guiwei; Amann, Kerstin Ute; He, You-Wen; Neurath, Markus; Becker, Christoph; et al. (Gastroenterology, 2013)
The intestinal epithelium generates a barrier that protects mammals from potentially harmful intestinal contents, such as pathogenic bacteria. Dysregulation of epithelial cell death has been implicated in barrier dysfunction and in the pathogenesis of intestinal inflammation. We investigated mechanisms of cell-death regulation in the intestinal epithelium of mice. Conditional knockout mice (either inducible or permanent) with deletion of cellular FLICE-inhibitory protein (cFlip) or caspase-8 in the intestinal epithelium were analyzed by histology and high-resolution endoscopy. We assessed the effects of cFlip or caspase-8 deficiency on intestinal homeostasis. Expression of cFlip in the intestinal epithelium was required for constitutive activation of caspase-8 under steady-state conditions. Intestinal expression of cFlip was required for development; disruption of the gene encoding cFlip from the intestinal epithelium (cFlip(fl/fl) VillinCre(+) mice) resulted in embryonic lethality. When cFlip was deleted from the intestinal epithelium of adult mice (cFlip(iΔIEC) mice), the animals died within a few days from severe tissue destruction, epithelial cell death, and intestinal inflammation. Death of cFlip-depleted intestinal epithelial cells was regulated extrinsically and required the presence of death receptor ligands, such as tumor necrosis factor-α and CD95 ligand, but was independent of receptor-interacting protein 3. cFlip deficiency was associated with strong up-regulation of caspase-8 and caspase-3 activity and excessive apoptosis in intestinal crypts. cFlip is required for intestinal tissue homeostasis in mice. It controls the level of activation of caspase-8 to promote survival of intestinal epithelial cells. BACKGROUND & AIMS METHODS RESULTS CONCLUSIONS
Keywords: CASP8; CFLAR; Fadd; Fadd-Like Apoptosis Regulator; Fas-associated protein with death domain; IEC; NEMO; NF-κB essential modulator; Rip; TNF; TUNEL; cFLIP; cellular FLICE-like inhibitory protein; intestinal epithelial cell; receptor interacting protein; terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate nick-end labeling; tumor necrosis factor